2017
DOI: 10.1177/1091581817728996
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Benzyl Alcohol, Benzoic Acid and its Salts, and Benzyl Benzoate

Abstract: Benzyl alcohol, benzoic acid and its salts, and benzyl benzoate function mostly as fragrance ingredients/preservatives in cosmetic products. The Cosmetic Ingredient Review Expert Panel previously established concentration limits for benzyl alcohol, benzoic acid, and sodium benzoate in cosmetics and determined that the available data were insufficient to support the safety of these ingredients during inhalation exposure. After reviewing newly available data, it was concluded that benzyl alcohol, benzoic acid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 79 publications
1
39
0
Order By: Relevance
“…Most of the identified compounds in this study have been reported to possess interesting biological activities ranging from antimicrobial, antioxidant, and anti-inflammatory as summarized in Table 4 . Benzyl benzoate is reported to function as fragrance ingredient, pesticides, pH adjusters, preservatives, solvents, and/or viscosity decreasing agents in cosmetic products [ 32 ]. Benzyl benzoate was identified in both Enterobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the identified compounds in this study have been reported to possess interesting biological activities ranging from antimicrobial, antioxidant, and anti-inflammatory as summarized in Table 4 . Benzyl benzoate is reported to function as fragrance ingredient, pesticides, pH adjusters, preservatives, solvents, and/or viscosity decreasing agents in cosmetic products [ 32 ]. Benzyl benzoate was identified in both Enterobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…Benzyl alcohol is generally safe excipient. However, studies have shown irritation potential on the skin [24]. It was found in just one drug (2 %).…”
Section: Resultsmentioning
confidence: 99%
“…The main component of P5 was benzyl benzoate (74.6%) ( Table 2 ), which is commonly used in the chemical, cosmetic and pharmaceutical industries [ 29 ]. This substance can be detected in natural conditions, being present in some plants, but it can also be obtained by chemical synthesis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%